2019
DOI: 10.1534/g3.119.400315
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Interaction of Nuclear and Mitochondrial Genotypes inDrosophila melanogaster

Abstract: Drosophila melanogaster , like most animal species, displays considerable genetic variation in both nuclear and mitochondrial DNA (mtDNA). Here we tested whether any of four natural mtDNA variants was able to modify the effect of the phenotypically mild, nuclear tko 25t mutation, affecting mitochondrial protein synthesis. When combined with tko 25t , the mtDNA from wild strain KSA2 produced pupal lethality, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…However, knocking down the OXPHOS cI-cV specific genes from the hemocytes did not affect the development rate or viability when compared to controls. Given the central role of hemocytes in the cell-mediated innate immunity, the observation of melanotic nodules in the mtKSA2 variant [23] and our finding that mtKSA2 had more hemocytes and potential hemocyte activation in the absence of infection (Fig 2A-A'), we focused our studies on larval hemocytes and the effect of decreased OXPHOS function in hemocytes on cell-mediated innate immune response.…”
Section: Mtksa2 Larvae Have a Higher Hemocyte Count And Elevated Hemo...mentioning
confidence: 99%
“…However, knocking down the OXPHOS cI-cV specific genes from the hemocytes did not affect the development rate or viability when compared to controls. Given the central role of hemocytes in the cell-mediated innate immunity, the observation of melanotic nodules in the mtKSA2 variant [23] and our finding that mtKSA2 had more hemocytes and potential hemocyte activation in the absence of infection (Fig 2A-A'), we focused our studies on larval hemocytes and the effect of decreased OXPHOS function in hemocytes on cell-mediated innate immune response.…”
Section: Mtksa2 Larvae Have a Higher Hemocyte Count And Elevated Hemo...mentioning
confidence: 99%
“…Formation of melanotic nodules is considered a sign of activated cell mediated innate immunity, and it usually involves the proliferation and aggregation of hemocytes, Drosophila blood cells (56). Furthermore, CYTB mutation bearing mitotype in a tko 25t nuclear background caused 100% pupal lethality, which is a first report of synthetic lethality between nuclear-mitochondrial interaction within a metazoan species (55).…”
Section: Disruption Of Mito-nuclear Crosstalkmentioning
confidence: 96%
“…In Drosophila, a mito-nuclear incompatibility resulted in energetically compromised flies that were more susceptible to infection by a bacterial pathogen (54). Salminen et al, identified an OXPHOS Complex III mutation D 21 N in D. melanogaster mitochondrial CYTB gene, that was shown to cause larval stage melanotic nodules in a healthy nuclear background (6%) and a significant increase (56%) of melanotic nodules when the mitotype was introgressed into a tko 25t nuclear background (55). Formation of melanotic nodules is considered a sign of activated cell mediated innate immunity, and it usually involves the proliferation and aggregation of hemocytes, Drosophila blood cells (56).…”
Section: Disruption Of Mito-nuclear Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, precise and synchronised coordination between the two genomes is required for proper assembly and function of the components of the electron transport chain and mitochondrial functions. Disruptions to this system -by mutations in the mitochondrial or nuclear counterparts -can have consequences to a wide-range of life-history phenotypes (10), and in severe cases leads to mitochondrial disease (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%